Shunt disconnection is less likely using a surgeon's knot compared with a surgical constrictor knot. (4th March 2021) - Okasha, Mohamed; Dobson, Gareth M.; Tsonis, Ioannis; Hussain, Mohammed; Ross, Nicholas
Abstract: Introduction: Ventriculo-peritoneal shunt malfunction is a common neurosurgical presentation, which may occur as a result of shunt disconnection at the level of the valve. Previous studies assessing ligatures have suggested that the constrictor knot is stronger in securing a ligature compared to the surgeon's knot. Our study compared the ability of each knot to secure shunt tubing to the valve. Methods: A medtronic shunt valve was secured to a peritoneal catheter using the surgeon's knot versus constrictor's knot. The weight and subsequent force (N) required to pull off the shunt tubing at the knot site were recorded. Results: The mean pull-off force was 11.7 N for the surgeon knot, and 8.9 N for the constrictor knot. There was significant difference in favour for the surgeon's knot compared to the constrictor knot. Conclusions: The surgeon's knot is significantly stronger than the constrictor knot for securing a peritoneal catheter to a CSF shunt valve.